Symbolic violence of cigarette Sales Promotion Girl (SPG) in Surabaya City - Habibi, Ahmad Wildan; Mas'udah, Siti; Suyanto, Bagong (Jurnal Sosiologi Dialektika, 2023)
Symbolic violence is a form of violence through the imposition of symbols and meaning. This study looks at how the symbolic violence that occurred in SPG Cigarettes in the city of Surabaya. The symbolic violence that occurs in SPG Cigarettes in the Work Environment has meanings and symbols that are cultivated by perpetrators of violence. This study uses the theory of symbolic violence from Pierre Bourdieu. Researchers used qualitative research methods with a phenomenological approach. Data collection techniques in this study included observation and in-depth interviews as well as general qualitative data analysis techniques from Creswell. This study found double violence in SPG Cigarettes, namely symbolic violence and sexual violence. This study also finds a new category of forms of symbolic violence adapted from Pierre Bourdieu's Theory. This study describes the habitus, capital, and realm that cause a person to commit symbolic violence on smoking SPGs. This study concludes that the symbolic violence that occurred against cigarette smokers has become a culture in several community groups. Women as ‘victims' of symbolic violence and sexual violence can fight so that this violence does not occur continuously and does not become a culture.